1980
DOI: 10.1111/j.1365-2133.1980.tb05690.x
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and HLA-Cw6

Abstract: The prevalence of histocompatibility antigen HLA-Cw6 was 72.7% in twenty-two patients with the guttate form and 45.9% in thirty-seven patients with the vulgaris form of psoriasis; the difference between these figures and the prevalence (7.4%) in 462 healthy blood donors in Finland is highly significant. The previously observed excess of several HLA-B locus genes might be secondary to their close linkage with the Cw6 gene. Hereditary factors appear more important in the guttate than in the vulgaris form of psor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
176
1
4

Year Published

1990
1990
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(183 citation statements)
references
References 2 publications
2
176
1
4
Order By: Relevance
“…Evidence suggests that activation of T cells precedes epidermal proliferation (7) and that CD8+ T cells predominate in epidermal lesions (1)(2)(3). Moreover, the HLA association of this disease is consistent with psoriasis being a T-cellmediated autoimmune phenomenon, with the highest relative risk associated with HLA-Cw6 (8), although other HLA class I and class II antigens also have a positive association with the disease (9). To determine whether cells infiltrating psoriatic lesions exhibit restricted T-cell receptor gene use and oligoclonality, which would suggest a response to tissue antigens, we examined epidermal T cells isolated from shave biopsies from psoriatic lesions.…”
mentioning
confidence: 82%
“…Evidence suggests that activation of T cells precedes epidermal proliferation (7) and that CD8+ T cells predominate in epidermal lesions (1)(2)(3). Moreover, the HLA association of this disease is consistent with psoriasis being a T-cellmediated autoimmune phenomenon, with the highest relative risk associated with HLA-Cw6 (8), although other HLA class I and class II antigens also have a positive association with the disease (9). To determine whether cells infiltrating psoriatic lesions exhibit restricted T-cell receptor gene use and oligoclonality, which would suggest a response to tissue antigens, we examined epidermal T cells isolated from shave biopsies from psoriatic lesions.…”
mentioning
confidence: 82%
“…41 However, the exact location of PSORS1 gene remains controversial owing to extensive linkage disequilibrium across this region. Two genes lying within this interval have been intensively studied with respect to their role in psoriasis susceptibility.…”
Section: Psors1mentioning
confidence: 99%
“…14 The HLA region has been thoroughly examined in many studies, and associations with sub-classes of HLA such as B13, Bw57, Cw6 and DR7 have been reported. [19][20][21] We have found a strong correlation between the presence of Cw6 and early onset in this family material. 22 A number of studies have shown linkage to the HLA region, 13,16,[23][24][25] as does our patient material.…”
Section: Introductionmentioning
confidence: 92%